PENGEMBANGAN CMS TODOYU SEBAGAI CMS MANAJEMEN PROYEK VERSI INDONESIA - Shomad, Abdush; susilo, dahlan; retnoningsih, dwi (Gaung Informatika, 2014)
Todoyu  is  a  web  based  system  for  project  management,  time  tracking,  and  billing agencies  specifically  tailored  to  the  needs  of  small-medium  sized  services  such  as lawyers,  engineers  and  architects,  services,  advertising  and  PR  agencies.  Todoyu improve  billing  accuracy  and  timeliness,  saving  companies  time  and  money,  and remove  the  risk  of  the  billing  process.  The  final  task  is  to  develop  the  CMS  Todoyu Todoyu CMS Version 2.3 Indonesia. The achievement  of this final project is described as follows: (1) The development of the final project successfully added language option Indonesia the Local Package. (2) The development of the final project is successfully making Todoyu responsive CMS display when accessed from mobile devices. (3) Based on the results of testing the system on this final can be concluded that the development of this project is based on the F test with 0,025 siknifikansi meningkatkat WebQual total assessment score, while the T test based on variable Usability improved quality.